Health Informatics Education in the Third World - Rienhoff, O. (Methods of Information in Medicine, 1989)
The state of the art is summarized showing many efforts but only few results which can serve as demonstration examples for developing countries. Education in health informatics in developing countries is still mainly dealing with the type of health informatics known from the industrialized world. Educational tools or curricula geared to the matter of development are rarely to be found. Some WHO activities suggest that it is time for a collaboration network to derive tools and curricula within the next decade.
Keywords: Education; Curriculum; Ambulatory Care Systems; Transportability of Program